Risk Management and Measuring Productivity with POAS – Point of Act System - Akiyama, M. (Methods of Information in Medicine, 2007)
Objectives: The concept of our system is not only to manage material flows, but also to provide an integrated management resource, a means of correcting errors in medical treatment, and applications to EBM (evidence-based medicine) through the data mining of medical records.Methods: Prior to the development of this system, electronic processing systems in hospitals did a poor job of accurately grasping medical practice and medical material flows. With POAS (Point of Act System), hospital managers can solve the so-called, “man, money, material, and information” issues inherent in the costs of healthcare.Results: The POAS system synchronizes with each department system, from finance and accounting, to pharmacy, to imaging, and allows information exchange. We can manage Man (Business Process), Material (Medical Materials and Medicine), Money (Expenditure for purchase and Receipt), and Information (Medical Records) completely by this system.Conclusions: Our analysis has shown that this system has a remarkable investment effect-saving over four million dollars per year-through cost savings in logistics and business process efficiencies. In addition, the quality of care has been improved dramatically while error rates have been reduced – nearly to zero in some cases.
Keywords: Point of care systems; hospital information systems; hospital equipment and supplies; hospital financial management; risk management